Boundary objects, knowledge integration, and innovation management: A systematic review of the literature - Caccamo, Marta; Pittino, Daniel; Tell, Fredrik (Technovation, 2023)
Enabling collaboration across disciplines, business functions, departments, organizations, and industries is a critical innovation management challenge. Successful innovation depends on effective knowledge integration among diverse actors. The concept of boundary objects to achieve knowledge integration has gained increasing popularity within innovation management. Despite the growing relevance, existing literature reviews about boundary objects are sparse. This review examines how boundary objects enable knowledge integration through a systematic analysis. An integrating framework of the scholarship on boundary objects links existing contributions to key theoretical perspectives on the study of boundary spanning for knowledge integration. Relevant publications are identified through a systematic literature review and discussed according to three themes: information processing, cognitive, and learning perspective on knowledge integration. Potential contributions to broader theorizing are highlighted in relation to three innovation settings: cross-functional collaboration, open innovation, and staged product development processes. •Collaboration across diverse actors is a critical challenge of innovation management.•Effective knowledge integration is necessary to innovate successfully.•Boundary objects work as interfaces for knowledge integration.•Existing literature about boundary objects is sparse.•A systematic analysis of boundary objects' literature helps innovation management.